(untitled) (Research, Society and Development, 2021)
Objective: To identify the approaches adopted by physical therapists for the prevention and treatment of intestinal constipation in pregnant women. Methodology: This is a descriptive and exploratory research with a qualitative approach, which was carried out in person, in an online format. The study population was represented by physical therapists working in the area of pelvic physical therapy in the city of Vitória da Conquista - BA. An online questionnaire developed by the researchers on the Google Forms platform was used as an instrument, containing questions to characterize the sociodemographic and occupational profile of the participants. Followed by questions directed to the topic under study where participants were able to share in writing, their experiences and behaviors adopted in the prevention and treatment of women who have IC during pregnancy. Results: Five female physiotherapists, aged 24 to 44 years old, answered the questionnaire, most of whom had a specialist title in the field of Pelvic Physiotherapy and reported having knowledge and mastery of the situation under study. Participants shared common techniques for the prevention and treatment of IC in pregnant women. Conclusion: The results of this research showed that the approaches used by physical therapists combined with the involvement of the multidisciplinary team are effective to prevent and treat constipation in pregnant women.